Isolation, cloning and sequence analysis of lactate dehydrogenase gene from Theileria annulata - Erdemir, A.; Aktas, M.; Dumanli, N.; Turgut-Balik, D. (Wiley-Blackwell Publishing, Inc, 2010)
[Abstract Not Available]
35th Congress of the Federation-of-European-Biochemical-Societies -- JUN 26-JUL 01, 2010 -- Gothenburg, SWEDEN